Managing participatory communication for climate adaptation in The Indonesia Climate Justice Network - Rahman, Azizul; Maryani, Eni; Ariestya, Angga; Syahidah, Sitti Aminah (Manajemen Komunikasi, 2025)
Climate change significantly threatens the sustainability of local communities, particularly those whose livelihoods remain closely tied to natural resources. Addressing this issue requires adaptation strategies that are not only scientifically grounded but also rooted in local experiences and cultural values. The present study seeks to examine the role of participatory communication in strengthening the adaptive capacity of communities confronting climate risks. This research is centered on the INCLINE Workshop (Indonesian Climate Justice Network) convened in Bali in March 2025, which involved participants from diverse backgrounds, including coastal, upland, and farming communities. Employing a qualitative case study design, the study applied thematic analysis to documents generated during the workshop, such as discussion records, issue mapping outputs, and community action plans. The findings reveal that local communities tend to interpret climate change through lived realities rather than technical terminology for instance, shifts in planting seasons, water scarcity, or the decline of traditional resources. Participatory communication emerges as an effective mechanism for fostering critical awareness, cultivating ecological solidarity, and encouraging grassroots adaptation practices. Examples include bamboo conservation initiatives, integrated waste management, and the revitalization of traditional food systems that support both resilience and cultural continuity. However, there are barriers such as limitations in village regulations, unequal access to information, and the exclusion of women in decision-making processes. The study’s conclusions emphasize that contextual, horizontal, and dialogic communication is a crucial foundation for fair and sustainable climate adaptation strategies.